2018
DOI: 10.3389/fmicb.2018.01475
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Antimicrobial Function of a Dairy-Originated Probiotic, Propionibacterium freudenreichii, Against Multidrug-Resistant Salmonella enterica Serovar Heidelberg in Turkey Poults

Abstract: Antimicrobial potential of a dairy-origin probiotic bacteria, Propionibacterium freudenreichii, against multidrug-resistant Salmonella Heidelberg (SH) in turkey poults was determined in the current study. Employing in vitro experiments, two strains (subsp.) of P. freudenreichii: P. freudenreichii freudenreichii B3523 (PF) and P. freudenreichii shermanii B4327 (PS) were tested for their ability to resist low pH (2.5) and bile salts (0.3%). In addition, the ability of the strains to adhere to and invade avian ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Compared to the antibiotic-resistant parent strains, probiotic-treated S. Heidelberg showed reduced multiplication, motility, and adhesion on intestinal epithelial cells. Follow-up in vivo study revealed that supplementation of P. freudenreichii to 14-day turkey poults resulted in reduced pathogen colonization in the cecum [ 163 ]. Also, P. freudenreichii in combination with a mannanoligosaccharide prebiotic and a Salmonella -specific vaccine was found to be effective in reducing cecal colonization of S. Heidelberg in 7-week and 12-week old turkeys (unpublished data).…”
Section: Ongoing Studies With Alternative Interventions Against Mumentioning
confidence: 99%
“…Compared to the antibiotic-resistant parent strains, probiotic-treated S. Heidelberg showed reduced multiplication, motility, and adhesion on intestinal epithelial cells. Follow-up in vivo study revealed that supplementation of P. freudenreichii to 14-day turkey poults resulted in reduced pathogen colonization in the cecum [ 163 ]. Also, P. freudenreichii in combination with a mannanoligosaccharide prebiotic and a Salmonella -specific vaccine was found to be effective in reducing cecal colonization of S. Heidelberg in 7-week and 12-week old turkeys (unpublished data).…”
Section: Ongoing Studies With Alternative Interventions Against Mumentioning
confidence: 99%
“…For turkey poults studies, 2 mL of 10 6 CFU/mL was administered to the turkey poults by passing a gavage tube through the mouth leading to the crop (crop gavage). Similarly, 10 mL of 10 5 and 10 7 CFU/mL MDR SH was administered to growing and finishing turkeys to obtain 10 6 CFU/growing turkey and 10 8 CFU/finishing turkey, respectively, by crop gavage ( Nair and Kollanoor Johny, 2018 ; Nair et al., 2018a , Nair et al., 2018b ; 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies conducted in our laboratory revealed that a dairy-originated probiotic bacterium, Propionibacterium freudenreichii subsp . freudenreichii B3523 ( PF ) was effective against multidrug-resistant Salmonella Heidelberg ( MDR SH ) in poults (2-week-old), growing (7-week-old), and finishing (12-week-old) turkeys ( Nair et al., 2018a , 2019 ; Nair and Kollanoor Johny, 2018 ; Nair et al, 2020 ). The PF supplementation resulted in 1.6-2.2 log 10 CFU/g reduction of MDR SH in the cecum of 2-week-old poults ( Nair and Kollanoor Johny, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two strains were used; namely, P. freudenreichii freudenreichii B3523 (PF) and P. freudenreichii shermanii B4327 (PS). The analysis revealed that P. freudenreichii could be used as an alternative to antibiotics for preventing SH infections in poults [ 206 ]. Table 8 indicates probiotics use to combat bacteria.…”
Section: Probioticsmentioning
confidence: 99%